A feminist perspective to enhancing access to justice for women in The Gambia's transition : Lessons from Uganda - Roux, Mispa (University of Pretoria, 2023)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2023.